Pengaruh jaringan wirausaha terhadap minat beli konsumen UMKM kue serta peran mediasi e-WOM dan buzz marketing - Kurniawan, Brahma Wahyu; Kusumawardani, Mawar Ratih; Balriq, Muhammad Hussein Basri (Jurnal Manajemen Bisnis dan Kewirausahaan, 2025)
To analyze the influence of entrepreneurial networks on consumer purchasing interest by considering the mediating role of electronic word of mouth (e-WOM) and buzz marketing in small and medium-sized cake businesses in Kediri. Small and medium-sized businesses, as the main drivers of the regional economy, face major challenges in developing effective and efficient promotional strategies. From this perspective, this research is worthy of study. The variables of entrepreneurial networks mediated by Buzz marketing and e-WOM are still rarely used. The research method used a quantitative approach with positivism principles, through accidental sampling techniques on 140 SME consumers. Data was collected through questionnaires and analyzed using Partial Least Square (PLS) used SmartPLS 4.0. The results show that entrepreneurial networks have a significant effect on consumer purchase interest, while e-WOM has no direct effect or mediating effect. Conversely, Buzz marketing has a significant effect on purchase interest and is able to mediate the effect of entrepreneurial networks on consumer purchase interest. These findings emphasize the importance of Buzz marketing strategies as a relevant and consumer-accepted promotional tool, while e-WOM is underutilized in the context of this study. This research provides theoretical contributions regarding the effectiveness of digital promotion, as well as practical recommendations for MSMEs in utilizing entrepreneurial networks to optimize purchase interest through viral communication strategies.